O seguro de vida em grupo como relação de consumo - Gazel, Claudia Ferrari Kronka (2007)
The purpose of this paper is to study the group life insurance contract within the context of a consumer relationship, and, specifically, to investigate the possibility of characterizing the policyholder as a service provider (in the Brazilian Consumer Defense Code s legal definition) in his/its relationship with the insured. Divided into four parts, the paper initially addresses the general characteristics of insurance contracts. In addition, it analyses the peculiarities of group life insurance, mainly its complex contracting process. The third part is exclusively dedicated to the policyholder, the individual or legal entity that enters into a group policy in favor of a certain group of people, playing an important role in the management of the insurance. In the fourth part of the paper, the concepts of consumer, service provider and consumer relationship are reviewed, pursuant to the rules of the Brazilian Consumer Defense Code. Lastly, it is concluded in this paper that the relationship between policyholder and insured is a consumer relationship whenever the policyholder acts as an arm of the insurance company instead of representing the interests of the insured